2021
DOI: 10.3400/avd.cr.21-00030
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen Therapy Is an Effective Adjunctive Therapy to Manage Treatment-Resistant Venous Leg Ulcers

Abstract: We report five cases of venous leg ulcers (VLU) that were resistant to conservative therapy for 22-119 months and were eventually healed via hyperbaric oxygen therapy (HBOT). In one patient, VLU recurred four times and was managed using HBOT, each time. The VLU sizes ranged from 18 to 68 cm 2 before HBOT. HBOT was administered at 2.0 atmospheres absolute with 100% oxygen for 60 min per session, five sessions a week during hospitalization. All VLUs healed after 17-66 sessions of HBOT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In another clinical study, Suehiro et al showed the beneficial therapeutic effects of HBO in five cases of venous leg ulcers (VLU) that were resistant to conservative therapy. All VLUs were healed after 17-66 sessions of HBO therapy [44].…”
Section: Discussionmentioning
confidence: 94%
“…In another clinical study, Suehiro et al showed the beneficial therapeutic effects of HBO in five cases of venous leg ulcers (VLU) that were resistant to conservative therapy. All VLUs were healed after 17-66 sessions of HBO therapy [44].…”
Section: Discussionmentioning
confidence: 94%